Songs of A Caged Bird: A Glimpse into the Being of Youth Inside the Prison System - John Emmanuel Mendoza; Edward Daniel Mortalla; Laurence Lascuna Garcia (Jurnal Keperawatan Indonesia, 2021)
Understanding young inmates’ experiences are essential since their lives have been shaped by the impact of social exclusion. This study aimed to explore the meaning of the lived experiences of young adults inside the prison system. The phenomenological inquiry was utilized, which is grounded in Martin Heidegger’s philosophy. Semi-structured interviews were conducted with 18 to 29-year-old inmates incarcerated for at least one year. Through interpretative phenomenological analysis, four themes emerged: An Unfamiliar Melody (with two subthemes: Humming with Frustrations and Tunes of Solitude); The Eyes Outside the Cage; Turning Over a New Feather; and If My Wings Unclipped. The “songs” of the caged bird tell about the “meanings” of restricted freedom--from being able to dip its wings in the orange sun rays down to being tied in chains. Being held inside a prison limits a person from experiencing life as they should. Opportunities to soar high were taken away. The consequences caused them the fragility of emotions: frustration, loneliness, and humiliation; yet, they still have a speck of hope. Abstrak Nyanyian Burung dalam Sangkar: Sebuah Pandangan terhadap Kehidupan Remaja dalam Sistem Penjara. Memahami pengalaman narapidana berusia muda sangat penting karena kehidupan mereka yang terdampak oleh pengucilan sosial. Tujuan penelitian ini untuk mengeksplorasi makna dari pengalaman hidup orang berusia dewasa muda di dalam sistem penjara. Penelitian menggunakan pendekatan fenomenologis yang didasarkan pada filosofi Martin Heidegger. Pengumpulan data menggunakan metode wawancara semi-berstruktur dengan narapidana berusia 18 hingga 29 tahun yang sudah dipenjara setidaknya selama satu tahun. Berdasarkan analisis fenomenologi interpretatif, muncul empat tema, yaitu: An Unfamiliar Melody (dengan dua subtema: Humming with Frustrations dan Tunes of Solitude); The Eyes Outside the Cage; Turning Over a New Feather; dan If My Wings Unclipped. “Nyanyian” burung dalam sangkar yang menceritakan tentang “makna” kebebasan yang terbatas—mulai dari mencelupkan sayapnya di bawah sinar matahari jingga hingga diikat dengan rantai. Kondisi dipenjara membatasi seseorang untuk menjalankan kehidupan sebagaimana mestinya. Peluang mereka untuk terbang melambung tinggi dirampas. Hal ini menyebabkan emosi mereka rapuh: frustrasi, kesepian, dan penghinaan; tetapi, mereka masih memiliki setitik harapan. Kata Kunci: fenomenologi, frustasi, narapidana dewasa muda, sistem penjara